Anterior glenoid bone reconstruction and anterior latissimus transfer for failed Latarjet associated with irreparable subscapularis tear - Jean-David Werthel, MD, PhD; Robin Lévêque, MD; Bassem T. Elhassan, MD (JSES International, 2023)
Background: Management of combined persistent anterior glenoid bone deficiency with irreparable subscapularis tear can be very complicated and challenging especially if associated with arthritis. The objective of this study was to report the outcome of combined reconstruction of the anterior glenoid with bone autograft or allograft with additional anterior latissimus transfer to reconstruct irreparable subscapularis tear with or without humeral head replacement. Methods: Nineteen patients (average age 29 years old) who underwent open anterior glenoid bone reconstruction with iliac crest bone autograft or ostechondral bone allograft (distal tibia or glenoid allograft), with anterior latissimus transfer to reconstruct irreparable subscapularis tear with or without humeral head replacement were included in this study. Outcome measures included preoperative and postoperative pain score, visual analog scale, Subjective Shoulder Value, American Shoulder and Elbow Surgeons score, and Constant Score. Results: Out of the 19 patients, 5 patients underwent humeral resurfacing arthroplasty. Anterior glenoid bone reconstruction was performed with iliac crest bone autograft in 8 patients, glenoid osteochondral allograft in 7 patients, and tibial plafond in 4 patients. At mean 31-month follow-up of (13-63 months), 15 patients (79%) considered their shoulder stable and were able to return to their work and 14 (74%) patients returned to their sport activity. Redislocation had occurred in 1 of the 18 shoulders (5%), subluxation had occurred in 3 patients (16%) of the shoulders and apprehension was reported for 4 patients, 21% of the operated shoulders. All outcome measures showed significant improvement compared to before surgery. No intraoperative or immediate postoperative complications were observed. Four patients (21%) had to be revised to reverse shoulder arthroplasty. Conclusion: The combination of anterior latissimus transfer, anterior glenoid bone grafting with or without humeral head resurfacing is an effective salvage surgical reconstruction that can stabilize shoulders in the setting of recurrent anterior instability after a failed Latarjet with an irreparable subscapularis tear. This could be a potential alternative reconstruction option that might be offered to patients with this difficult problem. Long-term outcome is needed to better evaluate the validity of this technique.